The First Step to Apostasy?: (An Ethiopian Ruler’s Missive to the Sultan Baybars Re-interpreted) - Francuzov, Sergej Alekseevič (Scrinium, 2020)
A majority of the sources on medieval Ethiopia are written in the Gǝ‘ǝz language in the “genre” of history. However, some texts written in Arabic remain equally important. Among such texts the missive addressed by a ruler of Ethiopia to the Mamluk Sultan Baybars (known as al-Malik al-Ẓāhir) in AH 673 / AD 1274-75 is of considerable interest. The Ethiopian ruler can be identified as the founder of the Ethiopian Solomonic dynasty Yǝkunno Amlak. The text of this missive survived in three Arabic versions: in the Islamic “encyclopaedias” by al-Nuwayrī and al-Qalqashadī (resp. AH 730 / AD 1330 and AH 814 / AD 1412) and in the dhayl (continuation) to the Universal history by al-Makīn, compiled by the Coptic author al-Mufaḍḍal b. Abī’l-Faḍā’il in AH 759 / AD 1358. All three versions are almost identical, however, the version by al-Nuwayrī is the longest one and the closest to the original. The detailed analysis of this version supplied by the full translation into English made for the first time by the present author clearly shows that the person who wrote it was the amīr (commander) of the Amhara and not yet the king of Ethiopia. However, he had an intention to become himself with his people a subject of Baybars to obtain help from him against the Zagwe dynasty. As a consequence, the Ethiopian Christians would have been under the Muslim power. However, the Mamluk Sultan was less interested in that affair.